A case of congenital methaemoglobinaemia with secondary polycythemia - Shamsa Kanwal; Muhammad Aamir; Sobia Irum; Zujaja Haroon; Muhammad Usman Munir; Afshan Bibi (Journal of the Pakistan Medical Association, 2022)
Haemoglobin contains iron in a ferrous form. When the iron is oxidized, it is called Methaemoglobin (MetHb). MetHb leads to tissue hypoxia, cyanosis, and secondary polycythemia. Methaemoglobinaemia is acquired or congenital. In this case, a 22-years-old male patient presented with cyanosis, headache, and lack of concentration. Cyanosis was present since birth. His previous investigations showed polycythemia. He was misdiagnosed on multiple occasions and was undergoing venesections for polycythemia. On evaluation at a private clinic, an Oxygen saturation gap was noted between the results of the pulse oximeter and arterial blood gas analyzer. This raised suspicion on the presence of MetHb. He was referred to Air Force Institute of Pathology, Rawalpindi for further workup.The sample obtained for MetHb was chocolate brown in colour. Analysis was done via co-oximetry. A high level of MetHb (45.6%) was obtained. —Continue